Evaluation of lecturer in higher education curriculum based on the National Standards of Higher Education No. 44 of 2015 - Sundayana, I Made; Kusuma Dewi, Putu Dian Prima; Megaputri, Putu Sukma (Graduate School, Universitas Negeri Yogyakarta, 2019)
The quality of education is still a benchmark of human resources (HR) in each country. The current era of revolution 4.0 requires a curriculum that is innovative, creative, and based on the needs of market share and the world of work with the addition of several new literacies. This study aims to identify and evaluate the tertiary curriculum (higher education curriculum) that has been applied in a higher education institution of health sciences in Buleleng, which refers to the national standard of higher education no. 44 of 2015. The evaluation was based on input, process, and output. The method used was the mixed method by using questionnaires and focus group discussions on 32 lecturers from the three knowledge fields of midwifery, nursing, and pharmacy. The results show that of the four standards evaluated, the learning process standard and assessment standard need to get priority in improving the academic system at the institution. Both of these components must be immediately improved in terms of concepts and understanding so that the goals, achievements, and quality of graduates can still be improved and maintained. Internal discussions and workshops should be done regularly each semester to refresh pedagogical ability and understanding of the regulatory faculty curriculum.